The role of midwives in the implementation of maternal death review (MDR) in health facilities In Ashanti region, Ghana - Dartey, Anita Fafa (2015)
Magister Curationis - MCur === Background and Problem Statement: Maternal mortality is a global health issue, which mostly affects the developing countries. The United Nations (UN) member states have made a commitment to reduce maternal mortality by 75% by 2015. However, one of the biggest challenges in monitoring maternal deaths in Sub-Sahara Africa including Ghana, is the lack of adequate information for the accurate estimation of the maternal mortality rate (MMRate), and to identify causes of death. The World Health Organization (WHO) developed strategies and guidelines to assist countries to generate accurate information regarding maternal deaths. Maternal death review is one such strategy that was implemented in Ghana. Midwives are among the health workers who participate in the implementation of this strategy in different health facilities.However, what is not well understood is the role that midwives play in the implementation of Maternal Death Review (MDR).The purpose of the study: To explore and describe the roles that midwives play in the implementation of MDR in selected health facilities in Ghana‟s Ashanti Region.Methodology: A qualitative descriptive design was used to guide the research.Purposive sampling was conducted to select midwives who have been involved in maternal death review from the teaching, regional and district referral hospitals. Data was collected by conducting semi-structured individual interviews. Data saturation was reached after twenty interviews. Thematic Content Analysis was used to manage and analyse data. The Facility-based maternal death review model was used to assist the researcher to identify and organize the emerged themes. Ethical clearance was obtained from the University, as well as approval from the management of the health facilities prior to approaching the informants.Main findings: The results of this study indicate that midwives in Ghana‟s Ashanti Region are undertaking various activities and duties in all the stages of the Facilitybased maternal review model. The type of activities and duties undertaken by midwives varied according to their seniority and the level of the health facilities.Conclusion and recommendation: The findings of this study bring insight into the roles played by midwives in the implementation of the Facility-based maternal death review process in the health facilities in Ghana‟s Ashanti Region. These findings have a direct implication for the training and education of midwives. It is recommended that issues related to maternal death review methods and processes be included in the formal and continuing training and education of midwives. However, further research considering the training and practice development needs of midwives in respect of implementation of maternal death review is required.